The Beginning of Baby’s Ability to Speak: The Language Philosophy Point of View - Mundir Sutaji, Ahmad Aris; Suswanto, Suswanto (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
This research explores the structure of the human brain and the beginning of a baby's speech. The brain is divided into two hemispheres: the left hemisphere controls language functions, including spoken and written language, and the right hemisphere is responsible for image recognition and visual forms. A baby begins speaking before birth, learning language through words and utterances from their mother. Post-birth, they use crying, babbling, gestures, and emotional expressions. The baby must then go through three stages: pronunciation, vocabulary building, and sentence formation.